2010
DOI: 10.1016/j.taap.2009.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled diesel emissions alter atherosclerotic plaque composition in ApoE−/− mice

Abstract: Recent epidemiological studies suggest that traffic-related air pollution may have detrimental effects on cardiovascular health. Previous studies reveal that gasoline emissions can induce several enzyme pathways involved in the formation and development of atherosclerotic plaques. As a direct comparison, the present study examined the impact of diesel engine emissions on these pathways, and further examined the effects on vascular lesion pathology. Apolipoprotein E-null mice were simultaneously placed on a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 33 publications
2
66
0
1
Order By: Relevance
“…Atherogenesis, a specific form of arteriosclerosis in which there is thickening of the arterial wall due to the accumulation of calcium and fatty materials, was increased and production of ROS was elevated. Aortas from certain strains of DEEexposed mice showed increased markers of vascular remodeling as well as overall changes in plaque composition (Campen et al, 2010); filtration of PM from the exposure atmosphere did not alter the types of responses seen with emissions, although the intensity of some of these responses was reduced.…”
Section: Cardiovascular Morbidity-human Panel Studiesmentioning
confidence: 87%
“…Atherogenesis, a specific form of arteriosclerosis in which there is thickening of the arterial wall due to the accumulation of calcium and fatty materials, was increased and production of ROS was elevated. Aortas from certain strains of DEEexposed mice showed increased markers of vascular remodeling as well as overall changes in plaque composition (Campen et al, 2010); filtration of PM from the exposure atmosphere did not alter the types of responses seen with emissions, although the intensity of some of these responses was reduced.…”
Section: Cardiovascular Morbidity-human Panel Studiesmentioning
confidence: 87%
“…Sun et al (27,28) used an apolipoprotein E knockout (ApoE -/-) mouse model to show that long-term exposure to low concentrations of PM 2.5 (particles smaller than 2.5 µm in diameter) altered vasomotor tone, and increased tissue-factor expression, vascular inflammation and atherosclerotic burden in these animals. Research at the Lovelace Respiratory Research Institute (New Mexico, USA) in ApoE -/-mice has shown vascular remodelling and altered atherosclerotic plaque composition following PM 10 exposure and diesel emission exposure (29)(30)(31). The present study was designed to determine whether and how PM 10 exposure affected the architecture of existing atherosclerotic plaques and to determine whether the observed ultrastructure was consistent with the characteristics of a more vulnerable atherosclerotic plaque.…”
Section: Méthodologie : Les Lapins Whlh (N=8) Exposés à 5 Mg De Partimentioning
confidence: 93%
“…Several studies in the ApoE -/-mouse have shown the transcriptional upregulation of factors associated with vascular remodelling including MMP-3, -7 and -9 following PM 10 exposure (29,30), and MMP-9 following diesel exhaust exposure (31). Future work testing for colocalization of these MMPs with migrating foam cells in the WHHL rabbit model would be of interest.…”
Section: Figure 9) a Protruding Leukocyte Is A Macrophage-derived Foamentioning
confidence: 97%
See 1 more Smart Citation
“…Several groups explored the observed link between air pollution and the progression of atherosclerosis. In apolipoprotein E-null (ApoE 2/2 ) mice, Campen and colleagues simultaneously showed that exposure to DE resulted in dose-related alterations in gene markers of vascular remodeling and aortic lipid peroxidation in mice receiving a high-fat diet (35). As filtration of the PM did not significantly alter these vascular responses, they concluded that the gaseous portion of the exhaust was a principal driver (35).…”
Section: Mechanistic Studies In Animals or Cell-based Systemsmentioning
confidence: 99%